The reaction of the skin and its appendages in rheumatoid arthritis patients using subcutaneous methotrexate: A description of three cases - Yu. V. Muravyev; G. I. Gridneva; S. G. Radenska-Lopovok; N. I. Kharitonova (Научно-практическая ревматология)
The paper reports the development of the adverse events of the skin and its appendages due to subcutaneous methotrexate, which serve as a manifestation of its toxicity in patients with rheumatoid arthritis. It discusses the possible mechanisms of their occurrence, although both clinical presentations and histological changes are not specific.